Salmonella spp A Global Challenge - Lamas, Alexandre; Regal, Patricia; Manuel Franco, Carlos (IntechOpen, 2021)
Salmonella is one of the main bacterial pathogens worldwide. S. Typhi is responsible for typhoid fever via fecal-oral transmission through contaminated food and water, whereas nontyphoidal Salmonella is transmitted through the food chain. Typhoid fever is of particular concern in developing countries. This means that control measures and the development of effective vaccines are necessary. Infections caused by multi-drug resistant Salmonella strains are becoming increasingly common. This book presents a comprehensive overview of the genus of Salmonella, including information on vaccines, control measures, strain characterization, bacteriophages, and much more.